UPAYA PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) PADA KELAS IV SD NEGERI 001 UKUI SATU - Asnimar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the activity and motivation of students to learn social sciences is still low. This is shown in their behavior when following social sciences learning. Based on the test scores of the first half of social sciences with a minimum completeness criterion (KKM) of 65, it is known that 58% of students graduated KKM while 42% of students did not complete. Under these conditions, it can be concluded that student learning outcomes are still low. Researchers also conducted interviews with several students. Some students said that classroom conditions were not conducive, friends liked to make noise in the classroom, the way teachers delivered material was less clear, and students' laziness to study also caused low learning outcomes. The objective to be achieved in this research is to determine the application of cooperative learning Think Pair Share (TPS) in improving learning outcomes for social sciences in the fourth grade students of SD Negeri 001 Ukui Satu. This classroom action research (PTK) was planned in two cycles. Each cycle in action research consists of four stages, namely: (1) planning, (2) acting, (3) observing, and (4) reflecting. This study was conducted at SD Negeri 001 Ukui Satu in the fourth grade, while the timing of this research is in the second semester of the 2016 academic year. The subject of this classroom action research is the fourth-grade students consisting of 34 students, with 11 male students and 23 female students. Data collection techniques in this study include observation, testing, documentation, and interviews